MAKNA SIMBOL GERAK TARIAN TORTOR DALAM UPACARA PERKAWINAN SUB ETNIS BATAK TOBA DI KECAMATAN BALIGE KABUPATEN TOBA SAMOSIR PROVINSI SUMATERA UTARA - Pandiangan, Elita Br.; Tinambunan, WE. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Tortor is one of the art cultural of Batak dance which is moving entire body with therhythm by gondang, with the center of the movement of the hands and fingers, feet and legs,back and shoulders. Tortor dances are preserverd the existency which is always used inBatak Toba traditionals events including the wedding party. The research purposes is todetermine symbol meaning of tortor dance sign in a wedding party, to know how tounderstanding of the meaning of symbol meaning of tortor dance sign in a wedding party andto know the movements symbol meaning of tortor dance sign in a wedding party of batak tobasub-ethnic in balige district.This research uses qualitative descriptive method based on the fact in the field throughobservations, interviews and documentations. Location of the research took place in theBalige district with research schedule in May 2014 until July 2014. Informants in this studyamounted to 7 peoples. Data analysis technique is used interactive analysis model by datavalidity checking techniquesThe result of this research shows that tortor dance in a wedding party is art of Batakculture that has its own benefits, in spite of having unique to tell the meaning in dance, alsobecome a process of giving and receiving Batak custom in Dalihan Na tolu system throughnonverbal communication that uses of symbols. The the meaning was contained in themessage symbol of tortor dance in a wedding party is not only describeb by every movements,but also for music of tortor dance in wedding party which is called gondang. Understandingof the meaning of the message symbol is very important to understand instead of just simplyenjoy the aesthetic beauty of this dance but as Batak toba society should stil preserve theBatak culture which is hereditary. The survey results revealed that many people do not knowthe meaning of tortor dance in wedding party. The movements for women’s clothing havebeen wearing kebaya inside and the outside of clothing wrapped by ulos. Ulos that used havebeen modified be modern. In a wedding party in Balige district not using gondang music, butreplaced with a keyboard music, keyboard music selected which the reasons are morepractical and also more modern.Kata Kunci : Tortor, Simbol, dan Budaya Batak